2015
DOI: 10.1163/22134808-00002475
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Crossmodal Congruency Task for Measuring the Limits of Visual–Tactile Interactions Within and Between Groups

Abstract: The crossmodal congruency task (CCT) is a commonly used paradigm for measuring visual-tactile interactions and how these may be influenced by discrepancies in space and time between the tactile target and visual distractors. The majority of studies which have used this paradigm have neither mea sured, nor attempted to control, individual variability in unisensory (tactile) performance. We have developed a version of the CCT in which unisensory baseline performance is constrained to enable comparisons within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
15
2
Order By: Relevance
“…It is important to characterise NT participants used as a control group since individual differences in sensory and autistic traits may potentially mask between-group differences on behavioural measures. However, it should be noted that there were no significant correlations between AQ scores and tactile thresholds (although see Poole et al 2015), or the size of the CE at each SOA and position. This suggests that the null effect of group on the temporal modulation of visual-tactile interactions in Experiment 1 was not driven by the NT participants who reported above average levels of autistic traits.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…It is important to characterise NT participants used as a control group since individual differences in sensory and autistic traits may potentially mask between-group differences on behavioural measures. However, it should be noted that there were no significant correlations between AQ scores and tactile thresholds (although see Poole et al 2015), or the size of the CE at each SOA and position. This suggests that the null effect of group on the temporal modulation of visual-tactile interactions in Experiment 1 was not driven by the NT participants who reported above average levels of autistic traits.…”
Section: Discussionmentioning
confidence: 84%
“…A previous study reported a significant effect of temporal and spatial modulation of visual-tactile interactions in 13 NT participants (Poole et al 2015). In the present study we aimed to exceed this sample size to find a between groups effect and account for the heterogeneity likely in participants with ASC.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations